1998
DOI: 10.1111/j.1475-6803.1998.tb00693.x
|View full text |Cite
|
Sign up to set email alerts
|

The Intra‐industry Effects of Open Market Share Repurchases: Contagion or Competitive?

Abstract: We examine the extent to which announcements of open market share repurchase programs affect the valuation ofcompeting firms in the same industry. On average, although firms announcing open market share repurchase programs experience a significantly positive stock price reaction at announcement, portfolios of rival firms in the same industry experience a significant and contemporaneous negative stock price reaction. This suggests that perceived changes in the competitive positions of the repurchasing firms occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 15 publications
4
48
0
Order By: Relevance
“…For example, Lang and Stulz (1992) argue that the competitive effect is positively related to the degree of concentration. Erwin and Miller (1998) coincide with the theoretical prediction that competitive effects are inversely related to the intensity of competition because the abnormal return of one firm is extracted from others. Following Lang and Stulz (1992), this study uses the Herfindahl-Hirschman Index (HHI) as a proxy for the degree of industry concentration.…”
Section: Variable Selectionsupporting
confidence: 85%
“…For example, Lang and Stulz (1992) argue that the competitive effect is positively related to the degree of concentration. Erwin and Miller (1998) coincide with the theoretical prediction that competitive effects are inversely related to the intensity of competition because the abnormal return of one firm is extracted from others. Following Lang and Stulz (1992), this study uses the Herfindahl-Hirschman Index (HHI) as a proxy for the degree of industry concentration.…”
Section: Variable Selectionsupporting
confidence: 85%
“…Prior studies have documented that cash flow similarity, leverage, industry concentration, and the AR of the event firm are essential determinants of the intra-industry effects (Erwin and Miller, 2004;Lang and Stulz, 1992;Xu et al, 2006). Firm size and Profitability are also common control variables in stock market studies.…”
Section: Control Variablesmentioning
confidence: 98%
“…Many corporate events have been found to have intra-industry effects: corporate liquidations (Akhigbe and Madura, 2006), earning restatements (Xu et al, 2006), bankruptcy announcements (Lang and Stulz, 1992), stock repurchases (Erwin and Miller, 2004), and dividend reduction announcements (Impson, 2005). To the best of our knowledge, however, no study has been published on the intra-industry effect of corporate environmental violation, other than that in which Patten (1992) provided evidence that an Alaskan oil spill event posed a potential legitimacy threat to peer firms, which was reflected in the subsequent environmental information disclosure.…”
Section: Introductionmentioning
confidence: 99%
“…Research into share buy-backs (Erwin and Miller, 1998) has indicated that the majority of repurchases are conducted ''on market''; some 90 per cent of share buy-backs are conducted using this method. Open market repurchases usually (but not always) involve gradual programmes to buy-back shares over a period of time.…”
mentioning
confidence: 99%